Upaya Pembentukan Karakter Pemuda melalui Pendidikan di Tajaul Karomah Desa Situgadung Kabupaten Tangerang - Ariyanti, Eti; Wardani, Endang Susilo; Irawati, Laila (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid development of technology and information in today's era poses significant challenges for youth, particularly in shaping strong character and moral values. Responding to this issue, the Community Service Program (PKM) titled